Peering through the Kaleidoscope: Variation and Validity in Data Collection on Terrorist Attacks. (2nd July 2016) - Behlendorf, Brandon; Belur, Jyoti; Kumar, Sumit
ABSTRACT: The nature of underreporting terrorism in developing countries is often acknowledged but poorly understood. Focusing on India, we triangulate terrorist attacks captured across three media-based datasets (Global Terrorism Database, South Asia Terrorism Portal, Worldwide Incident Terrorism System) against official police records from Andhra Pradesh. Results suggest that media-based datasets capture the geographic prevalence of terrorism yet severely underestimate the frequency of violence, biasing toward lethal bombings. Considerable variation is present for attacks targeting specific classes or types of actors. Similar to other crimes, the results suggest that existing terrorism databases represent a select version of violence in these countries, discounting the prevalence and regularity of non-lethal violent activity.